Systematic Review and Meta-Analysis of Candidate Gene Association Studies With Fracture Risk in Physically Active Participants - Ryan-Moore, Edward; Mavrommatis, Yiannis; Waldron, Mark (Frontiers in Genetics, 2020)
Background: Fractures are common in physically active populations and genetic differences may mediate injury risk. Objective: To meta-analyse the pooled results of candidate gene association studies with non-osteoporotic fracture risk in physically active humans. Methods: Systematic searching of databases returned 11 eligible studies published in English. Pooled odds ratios (ORs) with 95% confidence intervals (CI) were produced using allele contrast, recessive and homozygote contrast meta-analysis models to evaluate associations of risk alleles in the COL1A1 (rs1800012), COL2A1 (rs412777), CTR (rs1801197), ESR1 (rs2234693 and rs9340799) LRP5 (rs3736228), VDR (rs10735810, rs7975232, rs1544410, and rs731236) genes with fracture incidence. Results: Eligible study quality was generally low (7/11) and no significant overall effect was found for any genetic variant with any comparison model (p > 0.05). A trivial reduction in fracture risk was found for female participants with the COL1A1 Sp1 (rs1800012) T allele (OR = 0.48, 95% CI = 0.25–0.91, p = 0.03, d = –0.18). Conclusions: No overall effect was found from the pooled results of included genetic variants on fracture risk in physically active participants. The COL1A1 Sp1 rs1800012 T allele may reduce fracture risk in physically active females but further high-quality research with sex-specific analysis is required. Trial Registration: (PROSPERO; CRD42018115008).